Prognostic factors in Taiwanese patients with penile‐invasive squamous cell carcinoma. Issue 10 (28th August 2015) - Geng, Jiun‐Hung; Huang, Shu‐Pin; Huang, Chao‐Yuan
Abstract: In Taiwanese patients, carcinoma of the penis is an uncommon disease. We retrospectively reviewed potential prognostic factors in Taiwanese patients with invasive‐penile squamous cell carcinoma (SCC). From 1997 to 2009, 52 patients were enrolled. The median patient age at diagnosis was 66.5 years and the peak incident occurred during the 6 th and 7 th decades of life. Thirteen patients (25%) died of penile cancer, with a mean follow‐up time of 45 months (interquartile range: 15–64 months). The 5‐year cumulative cancer‐specific survival rate was 81%, with 100% for those with Stage I, 90% for those with Stage II, 60% for those with Stage III, and 14% for those with Stage IV. Eleven variables, including grade, tumor, node, metastasis (TNM) stage, involvement of corpus spongiosum or corpora cavernosa, lymphovascular or perineural invasion, lymphadenectomy, and palpable lymph node, with p < 0.05 using univariate analysis were chosen for multivariate regression analysis. Three of these potential prognostic factors, including histological grade, distant metastasis, and lymphovascular invasion, remained statistically significant. Our study is the first report using the latest TNM classification (2009) to determine these potential predictors with penile SCC in Taiwan.